Implementasi Kebijakan Insentif Pajak Penghasilan Final Usaha Mikro Kecil Menengah Ditanggung Pemerintah Pada Kantor Pelayanan Pajak Pratama Bekasi Utara Tahun 2020 - Rendy Galih Ardiyanto; Novianita Rulandari; Pentanurbowo Pentanurbowo (Jurnal Ilmu Administrasi Publik, 2022)
To cope with the impact of the Covid-19 pandemic, it is necessary to extend the time for tax incentive provision during the national economic recovery period so that the policy regulated in the Minister of Finance of the Republic of Indonesia PMK-110/PMK.03/2021 can be used more widely. The tax incentives are also expected to be utilized by UMKM business actors in the context of national economic recovery due to the Covid-19 pandemic. This research was conducted using a descriptive qualitative method, where data were obtained through observations, documentation, and interviews with MSME actors in North Bekasi and employees of the Primary Tax Office of North Bekasi. This study aims to determine the implementation of the government-borne MSME final income tax incentive policy at the Primary Tax Office of North Bekasi in 2020. The theory used was the implementation theory of Merilee S. Grindle. The results of the study show that to date the government-borne final income tax incentive policy for MSMEs affected by the Covid-9 pandemic has been effective in restoring the national economy. However, there are still obstacles in its implementation, such as the low understanding of the taxpayers towards government-borne MSME final income tax incentive and tax digitization, poor internet signal, and the delay or failure of taxpayers in reporting their taxes, resulting in them not getting the tax incentives.